The Effect of Environmental Performance, Media Exposure, and Corporate Governance on Corporate Social Responsibility Disclosure - Nala Rizka Kamalia; Kartika, Indri (Majapahit Journal of Islamic Finance and Management, 2025)
Corporate Social Responsibility (CSR) reflects a company’s ethical responsibility in managing environmental and social impacts as part of sustainable governance. This study examines the influence of Environmental Performance, Media Exposure, Independent Board of Commissioners, and Audit Committee on CSR disclosure. The research uses 189 manufacturing company samples listed on the IDX during 2021–2023, selected through purposive sampling. Data were analyzed using Multiple Linear Regression. Results show that Environmental Performance, Media Exposure, and Audit Committee positively affect CSR disclosure, while Independent Commissioners have a negative effect. The limited timeframe and sampling method may restrict generalizability. Future research should consider longitudinal data and broader variables such as firm growth. Companies are encouraged to adopt global standards like GRI to enhance CSR quality beyond reputational concerns.